Boosting EFL Public Speaking: How Preparedness and Self-Confidence Impact Willingness to Communicate - Cenderato, Cenderato (Universitas PGRI Adi Buana Surabaya, 2026)
This study investigates the impact of preparedness, self-confidence, and willingness to communicate (WTC) on public speaking among 52 first-semester EFL students at STAKatN Pontianak. Utilizing a correlational design, the results indicate that both preparedness and self-confidence significantly drove WTC. Specifically, preparedness—encompassing communicative competence and affective readiness—enables oral production through situational preparedness, while self-confidence reduces anxiety and enhances perceived ability across classroom and digital settings. Together, these factors create a reciprocal cycle: they diminish avoidance behaviors and foster positive emotional states like grit, leading to long-term fluency gains. Practically, these findings suggest that educators should prioritize